Atypical form of non-Langerhans histiocytosis with disseminated brain and leptomeningeal lesions. Issue 5 (1st November 2000) - Stojkovic, T; de Seze, J; Maurage, C-A; Rose, C; Hache, J-C; Vermersch, P
Abstract : An 18 year old girl presented with acute visual loss. T2 weighted brain MRI showed areas of hyperintensities in the thalamic nuclei, internal capsule, lentiform nuclei, the subarachnoidal spaces, and a retrobulbar infiltration. Analysis of CSF showed numerous foamy histiocytes without malignant cells, raised protein, and depressed glucose concentration. Biopsy of the right thalamus demonstrated aggregates of histiocytes with immunohistological and ultrastructural characteristics of non-Langerhans cell histiocytosis. The patient improved with chemotherapy and corticosteroids. After 3 months of treatment, CSF analysis showed no more histiocytes. Cytological examination of CSF can be helpful for the management of patients with extensive histiocytic infiltration.